PRINCIPAL COMPONENT ANALYSIS IN INBREDS OF MAIZE (Zea mays L.) - S. MALLIKARJUNA,; V. ROJA 1 , I. SUDHIR KUMAR,; S.K. NAFEEZ UMAR,; T. SRINIVAS, (The Bioscan, 2021)
The present study was carried out during kharif, 2018 using 49 maize inbred lines at Agricultural Research Station (ARS), Peddapuram, Andhra Pradesh. Principal Component Analysis (PCA) revealed first five principal components with eigen value greater than one. These principal components together accounted for 75.39 per cent of the total variability. The first Principal Component (PC1) contributed maximum towards variability (23.06%) followed by second (17.48%), third (14.66%) and fourth (11.52%) Principal Components, respectively. The characters, namely plant height, ear placement height, days to 50 per cent tasselling, cob length, grain yield plant-1, days to 50 per cent silking and cob girth contributed maximum for the variability. The results of scatter diagram revealed importance of hybridization between CML 1505, CML28708 and PDML 19-39 inbred lines with ADL 8070 and PDML15 inbreds for the production of heterotic and high yielding hybrids due to their diversity.